The Effect Enterprise Risk Management, Sustainable Banking Disclosure, Financial Inclusion on Firm’s Value - Wahyuningsih, Liya; Risman, Asep (Universitas Mercu Buana, 2025)
This research aims to determine the influence of Enterprise Risk Management, Sustainable Banking Disclosure and Financial Inclusion on Firms Value. The population in this research is banking sub-sector companies listed on the Indonesia Stock Exchange for the 2019-2023 period, totaling 9 companies according to the characteristics determined by the researcher. The sample used was 45 samples, calculated based on purposive sampling technique. The data for this research is collected through secondary sources, and the analysis is conducted using panel data regression with Eviews 12 software. The results of this research show that risk management has a positive effect on firm’s value, sustainable disclosure has a negative effect on firm’s value, and financial inclusion has no effect on firm’s value.Keyword: Risk Management, Sustainable Banking Disclosure, Financial Inclusion, Firm’s Value.